Development of an Art Therapy Module for Burnout and Self-Adjustment in K-Drama-Addicted Students - Elni Yakub; Isnaria Rizki Hayati; Amirah Diniaty; Siska Mardes; Najwa Adyani Dwitammi (Ta'dib, 2025)
The increasing phenomenon of academic burnout and low self-adjustment among students addicted to Korean dramas presents a serious challenge for guidance and counseling services in schools. This study aims to develop an Art Therapy module as an intervention to reduce academic burnout and enhance studentsÔÇÖ self-adjustment. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). Data were collected through observation, interviews, academic burnout questionnaires, self-adjustment scales, and expert validation in content, design, and language. Data analysis included product validity assessment, module practicality evaluation, and effectiveness testing using the Wilcoxon Signed Ranks Test. The results indicated that the module demonstrated a high level of validity (average >90%), excellent practicality (92%), and statistically significant effectiveness in reducing academic burnout (from 85.86 to 76.97) and improving student self-adjustment (from 83.46 to 99.00). The Wilcoxon test confirmed significant differences between pretest and posttest scores for both academic burnout (p = 0.000) and self-adjustment (p = 0.000). In conclusion, the Art Therapy module is valid, practical, and effective as a medium for group counseling services to support students in coping with academic burnout and enhancing self-adjustment affected by Korean drama addiction.